Methods of bremsstrahlung monitoring for photonuclear technologies - Karasyov, S.P.; Nikiforov, V.I.; Uvarov, V.L.; Shevchenko, V.A.; Shlyakhov, I.N. (Вопросы атомной науки и техники, 2006)
The paper describes the methods and devices proposed for measuring the main parameters of high-power highenergy bremsstrahlung sources. It has been suggested that space-energy characteristics of radiation should be investigated by the method of combined (γ, n) activation of a set of foils that have different energy thresholds of the reaction. In each energy range, the geometrical characteristics of the radiation field are reconstructed from the foil surface activity distributions. The last ones are determined through one-dimensional scanning of the foils by a specially designed detecting head that includes a linear matrix from collimated CdZnTe-base detectors. For a continuous monitoring of the bremsstrahlung power flow it is suggested that the method of feed-free secondary emission should be used, with a plane-parallel detector having two plates of different thickness as the base. A preliminary analysis of the geometry and applicability conditions of each of the detector systems was performed by the method of computer simulation based on the PENELOPE software system